Object-oriented databases - Khoshafian, Setrag (Wiley professional computing, 1993)
Offers a comprehensive overview of the concepts, capabilities and alternatives for the next generation database management systems (DBMS). Illustrates how object-oriented ideas of abstract data typing, inheritance and object identity can be integrated with database capabilities such as persistance, transactions and integrity to produce powerful object-oriented DBMS. Features numerous examples from recently introduced commercial products as well as prototype object-oriented databases.